FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT KEJADIAN ANEMIA PADA IBU HAMIL - Naftali, Greace; Simanjuntak, Maestro; Yustin Simanjuntak, Roy (Jurnal Kedokteran Methodist, 2022)
Background: Anemia is the most common health problem in the world, especially for pregnant women. Pregnant women who suffer from anemia in developing countries are generally thought to be due to iron deficiency. In pregnancy, the most common anemia disorder is iron deficiency anemia. Empty iron reserves in the body (depleted iron stores) is an iron deficiency anemia in which there is a lack of iron supply for erythropoiesis, resulting in reduced hemoglobin formation. Methods: The study used a literature review method using secondary data. Data were collected using documentation techniques. The supporting research journals used were 11 journals, both national and international journals with a publication deadline of the last 5 years and using Indonesian and English. In this study, the inclusion criteria were pregnant women. Conclusion: There is a relationship between nutritional status, adherence to consuming iron tablets and socioeconomic which are factors related to the incidence in pregnant women. There is no relationship between age and level of education of the mother with the occurrence of anemia in pregnant women.